Visibility to empowerment fostered using concept maps in the study of abstract biological concepts - Araújo-de-Almeida, Elineí; Santos, Roberto Lima (Seven Editora, 2024)
The concept mapping technique enables personal and collective autonomy, promoting the exercise of various cognitive skills, which favor creativity and logical thinking. Due to the importance of practices related to the construction of scientific texts, the objective of this article was to highlight products developed in the course of teaching and learning, using concept maps, as a way to signal evidence of empowerment in the study of little-known zoological taxa. The present investigation used the methodology of content analysis to examine the publications developed by students with the authors of this paper and associated researchers. Specifically, productions that used the conceptual integration tool to elucidate taxonomic, phylogenetic and ecological contents on neglected fauna groups were selected for analysis. The documents analyzed indicated that, by mobilizing the study of abstract concepts related to enigmatic invertebrates, with the elaboration of scientific writings disseminating biodiversity, an active participation of students is promoted. Experiences of this nature reflect evidence of empowerment in higher education, in addition to increasing the sense of belonging to biological diversity and its environmental interactions. DOI:https://doi.org/10.56238/sevened2024.014-020